Pasteurella multocida toxin: lessons learned from a mitogenic toxin - Hieke-Kubatzky, Katharina (Frontiers in immunology, 2022)
The gram-negative, zoonotic bacterium Pasteurella multocida was discovered in 1880 and found to be the causative pathogen of fowl cholera. Pasteurella-related diseases can be found in domestic and wild life animals such as buffalo, sheep, goat, deer and antelope, cats, dogs and tigers and cause hemorrhagic septicemia in cattle, rhinitis or pneumonia in rabbits or fowl cholera in poultry and birds. Pasteurella multocida does not play a major role in the immune-competent human host, but can be found after animal bites or in people with close contact to animals. Toxigenic strains are most commonly found in pigs and express a phage-encoded 146 kDa protein, the Pasteurella multocida toxin (PMT). Toxin-expressing strains cause atrophic rhinitis where nasal turbinate bones are destroyed through the inhibition of bone building osteoblasts and the activation of bone resorbing osteoclasts. After its uptake through receptor-mediated endocytosis, PMT specifically targets the alpha subunit of several heterotrimeric G proteins and constitutively activates them through deamidation of a glutamine residue to glutamate in the alpha subunit. This results in cytoskeletal rearrangement, proliferation, differentiation and survival of cells. Because of the toxin’s mitogenic effects, it was suggested that it might have carcinogenic properties, however, no link between Pasteurella infections and cell transformation could be established, neither in tissue culture models nor through epidemiological data. In the recent years it was shown that the toxin not only affects bone, but also the heart as well as basically all cells of innate and adaptive immunity. During the last decade the focus of research shifted from signal transduction processes to understanding how the bacteria might benefit from a bone-destroying toxin. The primary function of PMT seems to be the modulation of immune cell activation which at the same time creates an environment permissive for osteoclast formation. While the disease is restricted to pigs, the implications of the findings from PMT research can be used to explore human diseases and have a high translational potential. In this review our current knowledge will be summarized and it will be discussed what can be learned from using PMT as a tool to understand human pathologies.
Gesehen am 23.01.2023